Kaposi's sarcoma in an Ankylosing Spondylitis patient treated with Anti-Tumor Necrosis Factor-Alpha (Anti-TNF-α) Therapy - Selda Hakbilen; Dilek Tezcan; Sema Yilmaz (Turkish Journal of Internal Medicine, 2022)
Tumor necrosis factor-alpha (TNF-α) inhibitors are immunosuppressive agents used in a variety of inflammatory diseases, including rheumatoid arthritis (RA), spondyloarthritis, psoriasis, and inflammatory bowel disease (IBD). Kaposi’s sarcoma (KS) is an angioproliferative disease associated with the human herpes virus 8 (HHV-8). We present a 46-year-old male patient with ankylosing spondylitis (AS) treated with TNF-α inhibitor and developed KS during follow-up. The coexistence of anti-TNF-α treatment with KS is a rare condition. This case is presented to address this rare association. Therefore, keeping in mind KS, which is a type of skin tumor, in such HIV-negative patients in whom immunosuppressive agents are initiated, is essential in terms of early diagnosis, treatment, and prevention of complications.